Relationships between personality traits and perception of tactical knowledge in Brazilian female field hockey players - Nogueira da Gama, D. R.; Máximo de Souza, C. A.; Praxedes dos Santos, J. L.; do Espírito Santo, W. R.; Brandão Pinto de Castro, J.; Gomes de Souza Vale, R. (Kinesiology, 2022)
The present study aimed to investigate the relationships between personality traits and tactical knowledge of field hockey players. The sample consisted of 53 Brazilian female field hockey athletes. The collection instruments were the Big Five Personality Factors Inventory, the Self-Assessment Inventory of Tactical Skills in Collective Sports Games, and a sociodemographic questionnaire. The data were treated according to descriptive and correlational statistics. Percentage values were calculated when the variables showed significant differences. The normality and homogeneity of the data were verified by the Shapiro-Wilk and Levene tests, respectively. The partial correlation test, controlled by the position of the players, was used to analyze associations between the variables. A one-way ANOVA was applied to compare participants` age and practice time with their field positions. The Kruskal-Wallis test was used to compare the positions of the players. The value of p<.05 was adopted for statistical significance. As a result, a moderate positive correlation was obtained between practice time and age; a moderate negative correlation of Neuroticism with age and practice time; moderate positive correlations between practice time and declarative and procedural knowledge. The Openness exhibited moderate positive correlations with declarative and procedural knowledge. The midfield players had higher scores in Extraversion when compared to the defensive players. In Agreeableness, the midfield players had higher scores when compared to defense and attack. The study allowed concluding that Openness was associated with the tactical knowledge domain.